Chloride ion penetration into cracked UHPFRC during wetting-drying cycles - Matos, Ana Mafalda (2021)
The subject of this paper is the extent to which, during wetting–drying cycles, chloride ions can penetrate Ultra-high-Performance Fibre Reinforced Cementitious Composites (UHPFRC) specimens subjected to combined mechanical and environmental load. Pre-cracking was obtained by subjecting prismatic specimens (40 40 60mm3) to four-point bending until a predefined crack opening displacement (COD) is reached, using a dedicated test setup. Three target CODs were studied: 300, 350 and 400 μm. Exposure to a concentrated chloride solution (3.5% NaCl) was used as an environmental load. Specimens we subjected to wetting–drying cycles for one year. After this exposure period, the chloride penetration was characterised both qualitatively (by colourimetric analysis with silver nitrate) and quantitatively (by determining the chloride profile). The effect of damage level on chloride penetration and its impact on structures durability is discussed in the current paper.